2021
DOI: 10.3390/e23040468
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Statistical Reporting and Data Presentation in Predatory Dental Journals Was Lower Than in Non-Predatory Journals

Abstract: Proper peer review and quality of published articles are often regarded as signs of reliable scientific journals. The aim of this study was to compare whether the quality of statistical reporting and data presentation differs among articles published in ‘predatory dental journals’ and in other dental journals. We evaluated 50 articles published in ‘predatory open access (OA) journals’ and 100 clinical trials published in legitimate dental journals between 2019 and 2020. The quality of statistical reporting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
8
0
1
Order By: Relevance
“…Many of the studied PMCOA articles were from open access dental journals, indexed in PubMed (like BMC Oral Health and Clinical and Experimental Dental Research). Nieminen and Uribe [ 33 ] showed that in non-predatory (legitimate and indexed by established databases) open access dental journals, the presentation of results (particularly in tables and figures) was poorer than in more visible subscription-based dental journals but still better than in predatory (non-indexed) dental journals (from predatory publishers). Since referring to “data not shown” evidently is an obscure way of presenting results, it may be related to how results are presented in these studies in general.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studied PMCOA articles were from open access dental journals, indexed in PubMed (like BMC Oral Health and Clinical and Experimental Dental Research). Nieminen and Uribe [ 33 ] showed that in non-predatory (legitimate and indexed by established databases) open access dental journals, the presentation of results (particularly in tables and figures) was poorer than in more visible subscription-based dental journals but still better than in predatory (non-indexed) dental journals (from predatory publishers). Since referring to “data not shown” evidently is an obscure way of presenting results, it may be related to how results are presented in these studies in general.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study on the relationship between meat consumption and heart disease that fails to account for other factors that may contribute to heart disease, such as smoking or physical activity, or a study on the effectiveness of a new treatment for tuberculosis that fails to account for differences in disease severity or other factors that may influence treatment outcomes. 7 Errors in the application of statistical tests. Choosing the wrong test for a particular dataset affects the validation of observations during research.…”
mentioning
confidence: 99%
“…This means that they did not consider the fact that they tested multiple outcomes (blood pressure, heart rate, and cholesterol levels) and that there is a higher chance of obtaining a false positive result (i.e., a result that appears significant but is actually due to chance) when testing multiple outcomes. 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 Inappropriate use of p-values. p-Values are often misinterpreted as a measure of effect size or clinical relevance, when in fact they only indicate the probability of observing the study results by chance.…”
mentioning
confidence: 99%
See 2 more Smart Citations